2005
DOI: 10.1532/ijh97.04183
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 Variant B Infection in Adult Patients after Unrelated Cord Blood Transplantation

Abstract: Human herpesvirus 6 variant B (HHV-6B) infection was studied in 23 adult patients who underwent cord blood transplantation (CBT). HHV-6B DNA was detected by quantitative polymerase chain reaction analysis after CBT in the sera from 15 patients (65%) at day 14 or 15 (week 2), from 16 patients (70%) at day 21 or 22 (week 3), and from 3 patients (13%) at day 28 or 29 (week 4). HHV-6B DNAemia was found in none of the 20 patients examined at day 7 or 8 (week 1). The overall incidence of HHV-6B DNAemia reached 87% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
1
28
0
1
Order By: Relevance
“…The fact that HHV6 reactivation was more often seen after CBT has been described by others as well. [28][29][30][31] Moreover in our study, three of the five adults transplanted with CB in our study developed HHV6 reactivation. Additionally, differences in incidences between studies might be due to differences in conditioning intensity prior to HSCT, as found in our study.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The fact that HHV6 reactivation was more often seen after CBT has been described by others as well. [28][29][30][31] Moreover in our study, three of the five adults transplanted with CB in our study developed HHV6 reactivation. Additionally, differences in incidences between studies might be due to differences in conditioning intensity prior to HSCT, as found in our study.…”
Section: Resultsmentioning
confidence: 88%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]24,25,[28][29][30][31][33][34][35][36][37][38][39] Hentrich et al 25 reported a similar association between HHV6 reactivation and aGVHD, although no association was found between HHV6 reactivation and mortality. The association of HHV6 reactivation and aGVHD in the current study is comparable to the association found in other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Dzieciatkowski et al 68 Adult 4700 copies per mL detected in plasma 0.0% (0/3) 43.5% (10/23) de Pagter et al 69 Pediatric 4250 copies per mL detected in plasma 60% (9/15) 69.8% (30/43) Kitamura et al 34 Adult 4100 copies per 10 6 lymphocytes in whole blood 80% (8/10) 60% (3/5) Yamane et al 70 Adult 4200 copies per mL detected in plasma 92.3% (12/13) 30.3% (10/33) Tomonari et al 71 Adult 4200 copies per mL detected in serum 87% (20/23) 19% (4/21) Zerr et al 72 Mixed 425 copies per mL detected in plasma 100% (1/1) 46.8% (51/109) Sashihara et al 73 Pediatric 4100 copies per 100 000 PBMCs 100% ( All the five stem cell sources were from haploidentical donors. b Data evaluated after excluding HHV-6 'naive' patients (too young to have undergone primary HHV-6 infection).…”
Section: Discussionmentioning
confidence: 99%
“…It was described earlier in three studies but with a short follow-up post transplant. [9][10][11] Risk factors for developing HHV6 infection after allo-HSCT have been studied showing discordant results. Table 3 Kinetic of immune reconstitution after the transplantation, according to the source of graft Comparison of BM and PBSCs as SC source was shown to be 26 or not to be 27 a risk factor for HHV6 infection after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 In contrast, human herpes virus 6 (HHV6) reactivations appear to occur more frequently after CBT both in children 9 and in adults. 10,11 This report aimed to analyze the incidence, features and outcome of CMV, EBV and HHV6 infections in 55 consecutive adult patients receiving unrelated CBT or allo-HSCT from HLA-matched unrelated donors (MUD).…”
Section: Introductionmentioning
confidence: 99%